Biorational approaches to managing stored-product insects. - Phillips, Thomas W.; Throne, James E. (My University, 2009)
Stored-product insects can cause postharvest losses, estimated from up to 9% in developed countries to 20% or more in developing countries. There is much interest in alternatives to conventional insecticides for controlling stored-product insects because of insecticide loss due to regulatory action and insect resistance, and because of increasing consumer demand for product that is free of insects and insecticide residues. Sanitation is perhaps the first line of defense for grain stored at farms or elevators and for food-processing and warehouse facilities. Some of the most promising biorational management tools for farm-stored grain are temperature management and use of natural enemies. New tools for computer-assisted decision-making and insect sampling at grain elevators appear most promising. Processing facilities and warehouses usually rely on trap captures for decision-making, a process that needs further research to optimize.
Citation: Phillips, T., & Throne, J. (2010). Biorational Approaches to Managing Stored-Product Insects. Annual Review of Entomology, 55, 375-397. https://doi.org/10.1146/annurev.ento.54.110807.090451
Keywords: Biological control; Insect growth regulators; Pheromones; Physical control; Sampling; Decision-making